La amistad y el enamoramiento - Salazar Muoz, Jhuly (2019)
The present learning session, which is entitled Friendship and Amorousness, was developed in the of Personal Development, Civics and Citizenship for third grade of Secondary Education students from Educational Institution San Nicolas. The development of the learning session has been elaborated based on scientific and technical theories used in the pedagogical theoretical aspect, with the purpose that the students get to know and reflect on friendship and the processes that occur in the adolescent crush, since it will contribute to their development at this stage they are going through. _x000D_ _x000D_ During the session, students learned about friendship it is characteristics and how this process related to the processes of falling in love and the myths commonly thought about them.